Sugarcane Bagasse Fibers for Enhancing Moisture Susceptibility Properties in Stone Mastic Asphalt - Poornachandra Thejaswi; Jagadish Vengala; Manish S. Dharek; M. Manjunatha; Arjun Poudel (Advances in Materials Science and Engineering)
Stone mastic asphalt (SMA) mix amended with sugarcane bagasse fibers (SBFs) as a stabilizer was investigated experimentally in the present study. The SBF content in the combination mix was varied (0, 0.15%, 0.30%, 0.45% and 0.60%) to produce different mixtures. The prepared mixtures were then assessed for different properties, such as the Marshall stability, tensile strength, and draindown, which are crucial for the performance of the mix in flexible/bituminous pavements. The experimental results revealed enhanced stability and flow value, greater filling of voids in the bitumen, and reduced air voids in the prepared SMA mix amended with SBF. In addition, improvement in the tensile strength of the SMA mix amended with SBF was observed. An increase in the tensile strength ratio of the amended SMA mix was also observed. The susceptibility to the entry of moisture into the pores of the SMA mix was assessed by performing the draindown test, which revealed that the amended SMA mix exhibited reduced draindown due to the presence of SBF. Therefore, it was inferred that the inclusion of SBF into the SMA mix was beneficial for enhancing the stability and tensile strength of the mix and achieving higher resistance to moisture penetration. The present study demonstrated that the use of sugarcane bagasse as an active ingredient in the SMA mix would result in improved performance of flexible pavements while also reducing the waste burden of landfills and aiding in effective waste management.